PAKAPIN (Smart Pocket Board): Hands-On Learning Tool to Enhance Addition and Subtraction Skills in Second-Grade Students - Wida Rachmiati; Imas Masto'ah; Siti Mas Dhaifina Fahrana (International Journal of Research in Mathematics Education, 2026)
This study aims to develop and examine the effectiveness of the Smart Pocket Board (Pakapin) media in improving elementary school students’ mathematical problem-solving skills on addition and subtraction topics. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects were second-grade students at SDN Pekalongan II. Data were collected through tests, questionnaires, and expert validation, and analyzed using both quantitative and qualitative approaches, with effectiveness measured using the N-gain test. The results indicate that the Pakapin media achieved a feasibility level of 84.33%, categorized as feasible based on expert validation. The effectiveness test shows a significant improvement in students’ problem-solving skills, with an N-gain score of 0.71 (high category). Student and teacher responses reached 85.67% and 88%, respectively, both categorized as highly feasible. These findings suggest that Pakapin is effective in enhancing problem-solving skills through concrete and interactive learning. The study highlights the importance of manipulative media in supporting conceptual understanding and student engagement in elementary mathematics learning. Keywords: learning media ; Pakapin ; elementary mathematics ; addition and sustraction